Profile of Basic and Integrated Science Process Skills in Science Learning at Madrasah Ibtidaiyah Negeri - Farida, Laila; Suryajaya, Suryajaya; Suyidno, Suyidno (SEJ (Science Education Journal), 2023)
Science process skills underlie every student's activity in learning science at school and its application in technology and problem-solving. However, these skills are not trained enough in the Madrasah Ibtidaiyah Negeri (MIN). Therefore, the purpose of this study was to describe the profile of basic and integrated science process skills in MIN students. This research is a quantitative and qualitative descriptive study, where 79 students from 4 MINs in Hulu Sungai Utara were involved in working on a science process skills test instrument adapted from Suja (2010). The results showed the achievement of students' basic science process skills including measuring, questioning, communication, predicting, classifying, inferring, and observation; as well as the achievement of integrated science process skills including formulating hypotheses, planning experiments, interpreting data, and applying concepts with the lowest being 5.3% (hypothesizing) and the highest being 51.8% (measuring). Therefore; The profile of students' basic and integrated science process skills is still not good. Considering scientific process skills as the basic foundation in learning science, educators need to cultivate these skills in learning scientific concepts and their application in solving real life problems.